2005
DOI: 10.1088/0953-2048/18/7/008
|View full text |Cite
|
Sign up to set email alerts
|

Vortex pinning and slow creep in high-Jc MgB2thin films: a magnetic and transport study

Abstract: We have investigated the pinning of vortices in high-J c films of polycrystalline MgB 2 , by studying the dependence of current density J on electric field E using both magnetic and transport methods. Precursor films of amorphous boron, deposited on sapphire substrates, were converted to 0.6 µm thick MgB 2 by post-annealing in the presence of Mg vapour at 890 • C for 1 h. In magnetic studies, a SQUID magnetometer was used conventionally to determine the induced current density by the Bean model. The decay of J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
29
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 49 publications
11
29
1
Order By: Relevance
“…By compiling results from the literature for different superconductors, we reveal a cogent picture of this limitation and find few materials, including our Ba122:P film, MgB2 38,39 , and YBCO, with measured creeps rates near our proposed limit (Fig. 3b).…”
Section: S(t) Data From Ybco Samples With Different Microstructures (mentioning
confidence: 87%
“…By compiling results from the literature for different superconductors, we reveal a cogent picture of this limitation and find few materials, including our Ba122:P film, MgB2 38,39 , and YBCO, with measured creeps rates near our proposed limit (Fig. 3b).…”
Section: S(t) Data From Ybco Samples With Different Microstructures (mentioning
confidence: 87%
“…In this thesis equation (3.1) is exclusively used as a tool which simplifies computations. In fact, for MgB 2 thin films n can be very large, Thompson et al [55] found n = 78 at T = 25 K and B = 1 T. At lower temperature and field the value would be even larger. Along with the fact that the experiments described here typically takes only a few minutes to complete, it should be expected that creep effects can be safely ignored.…”
Section: Superconductivity Rudimentsmentioning
confidence: 98%
“…While the large coherence length and the size of the as grown point defects in MgB 2 enables strong grain boundary pinning, the larger anisotropy leads to greater U 0 at low fields. The magnitude of U 0 at low fields is given by U 0 ~ φ 0 2 ξ/48 π 2 λ 2 [17]. For MgB 2 using the value ξ ∼ 5 nm and λ ~ 100 nm [22] U o is estimated to be to be ~ 7400 K where as for the case of NbSe 2 with ξ ∼ 2.3 nm and λ ~ 230 nm, U o is calculated to be ~ 1000K.…”
Section: Introductionmentioning
confidence: 97%
“…In Figure 4 we plot the activation energy U o , determined from the magnetoresistance study versus applied magnetic field. Following Thompson et al [17], we fit the data using the equation…”
Section: Introductionmentioning
confidence: 99%